Morphologies of omega band auroras - Natsuo Sato; Akira Sessai Yukimatu; Yoshimasa Tanaka; Tomoaki Hori (Earth, Planets and Space, 2017)
Abstract We examined the morphological signatures of 315 omega band aurora events observed using the Time History of Events and Macroscale Interactions during Substorm ground-based all-sky imager network over a period of 8 years. We find that omega bands can be classified into the following three subtypes: (1) classical (O-type) omega bands, (2) torch or tongue (T-type) omega bands, and (3) combinations of classical and torch or tongue (O/T-type) omega bands. The statistical results show that T-type bands occur the most frequently (45%), followed by O/T-type bands (35%) and O-type bands (18%). We also examined the morphologies of the omega bands during their formation, from the growth period to the declining period through the maximum period. Interestingly, the omega bands are not stable, but rather exhibit dynamic changes in shape, intensity, and motion. They grow from small-scale bumps (seeds) at the poleward boundary of preexisting east–west-aligned auroras, rather than via the rotation or shear motion of preexisting east–west-aligned auroras, and do not exhibit any shear motion during the periods of auroral activity growth. Furthermore, the auroral luminosity is observed to increase during the declining period, and the total time from the start of the growth period to the end of the declining period is found to be about 20 min. Such dynamical signatures may be important in determining the mechanism responsible for omega band formation.